Building Human Resources Characteristics in Public Services: A Phenomenological Study on Civil Servants - Muniroh, Muniroh; Pawenary, Pawenary (Majalah Ilmiah Bijak, 2025)
This study aims to understand, analyze and describe the focus of Building Characteristics of State Civil Apparatus Employees in carrying out their duties and functions as public service lecturers - state servants who are required to serve student learning, research and community service in university and government environments. The method used by the researcher in this study is a Qualitative method with a Phenomenological Study approach. The data collection technique is based on secondary data processes, namely books, scientific journals, laws and regulations and seminar results as well as empirical data, namely; through the process of observation and interviews. The research informants are Academic Staff, Students and Lecturers of State Civil Apparatus Employees at Esa Unggul University and Lecturers at government higher education institutions.The results of the study found by the researcher, that "Building the Character of State Civil Apparatus Employees or Civil Servants is not easy to quickly change the characteristics of nature, character, behavior and motivate to build public services. First. ASN/PNS employees have characteristics if they carry out and implement laws and regulations and standard operating procedures (SOP) of government organizations. Second. State Civil Apparatus Employees are committed to implementing the Pledge (oath) in implementing laws and regulations. Third. ASN employees have a responsibility to the development and progress of the nation, especially universities and to distribute the moral values of the nation and the unitary state of the Republic of Indonesia. Fourth. Building cooperation between government institutions and other universities - for the activities of the Tri Dharma of universities and Fifth. Collaborative in carrying out public services that are trustworthy, have integrity, are professional and independent. Changing the character of State Civil Apparatus employees requires a strong leader, who has the capacity, integrity, professionalism and expertise in organizing and running the wheels of government (universities) and is able to control the employees of the institutions they lead ".